The opportunities and challenges of public policy communication in the context of digital transformation in Vietnam - Nguyen Nghi Thanh (Journal of State Management, 2024)
This research critically examines the impact of digital transformation on public policy communication in Vietnam, focusing on clarifying both the opportunities and challenges presented by this shift. It highlights Vietnam's strategic drive towards a digital economy by 2030 and identifies a notable research gap in understanding how digital transformation can simultaneously enhance and complicate public communication. The study aims to delineate effective strategies for leveraging digital platforms to improve engagement while addressing potential drawbacks such as the digital divide, privacy concerns, and misinformation. Results reveal that enhancing digital literacy, implementing robust cybersecurity measures, and developing inclusive communication strategies are crucial. The implications for policymakers are significant, suggesting that a comprehensive approach to digital transformation is essential for achieving more effective governance and active citizen participation in Vietnam.